Analysis of Madrasah Ibtidaiyah Teachers' Reflections on The Implementation of Akmi Follow-Up Workshop - Zuhriyyah Hidayati; Abu Amar (Rihlah Review: Jurnal Pendidikan Islam, 2023)
One indicator to measure the success of training activities can be seen from the participant's responses to the implementation of the training. This response can be obtained through self-reflection from participants at the end of the training or workshop. This research aims to determine the response of madrasah ibtidaiyah teachers to the implementation of the AKMI Follow-up Workshop organized by the Directorate General of Islamic Education, Ministry of Religion of the Republic of Indonesia through self-reflection activities scheduled in the last session of this activity. The workshop activity itself is a continuation of the implementation of the Asesmen Kompetensi Madrasah Indonesia (AKMI) for class V madrasah ibtidaiyah students that aims to equip teachers in madrasas to read the meaning of AKMI results for further follow-up by these teachers. This research uses a descriptive qualitative method with a questionnaire method with open questions. The results of the questionnaire showed that the majority of madrasah ibtidaiyah teachers who took part in the AKMI Follow-up Workshop responded positively to the implementation of the workshop. Things that MI teachers thought were new to them in this workshop were related to the four literacies material in AKMI, learning innovations, integrating the four literacies in AKMI in learning, and how to prepare scenarios for this integration. Some things that are considered not yet mastered by teachers are linking the four literacies into learning, understanding the competency achievements (CK) of each literacy, and arranging them in a learning scenario. To overcome this, teachers are committed to continuing to learn and deepen the workshop materials that are available on the LMS.